Analysis Of The Contribution Of Muscle Explosive Power Training Management To Smash Quality In Badminton - Kurnia Taufik (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2025)
Badminton is a sport that requires a combination of technical skill and physical performance. Smash, one of the main attacking techniques, demands excellent explosive power from the upper and lower extremities. This study aims to analyze the relationship between the explosive power of the arm and leg muscles with smash ability in badminton players of PB Angkasa Jaya Sumbawa. The method used was a correlational study with a population of 12 athletes as total sample. Arm muscle power was measured using the Two-Handed Medicine Ball Put Test, leg power using the Vertical Jump Test, and smash ability through a field-based shuttlecock accuracy test. The results showed a strong correlation between arm explosive power and smash performance (r = 0.719), while leg muscle explosive power alone did not show a significant relationship (r = 0.547). However, when both variables were analyzed together, the correlation was very strong (R = 0.798). These findings suggest that training programs should prioritize the integration of upper and lower body explosive training to improve smash effectiveness in badminton.